Frequency‐dependent seed predation by rodents on Sonoran Desert winter annual plants. Issue 1 (18th December 2017) - Horst, Jonathan L.; Venable, D. Lawrence
Abstract: Numerous mechanisms may allow species to coexist. We tested for frequency‐dependent predation, a mechanism predicted by theory and established as a foraging behavior for many types of animals. Our field test included multiple prey species exposed in situ to multiple predator species and individuals to determine whether the prey species experienced predation patterns that were frequency dependent. The prey were seeds of three species of Sonoran Desert winter annual plants while the predator species were a guild of nocturnal seed foraging heteromyid and murid rodents that co‐occur naturally in the same community as the desert annuals at Tumamoc Hill near Tucson. Seeds of one species were much preferred over the other two. Nonetheless, we found the net effect of rodent foraging to be positively frequency dependent (the preference for each species is higher when it is common than when it is uncommon) as has been previously hypothesized. This frequency‐dependent predation should function as a species coexistence promoting mechanism in concert with the storage effect that has been previously demonstrated for this system.